Pengalaman Perawat dalam Program Peningkatan Pendidikan Formal - Agnes Rini Eka Wulandari; Rr. Tutik Sri Hariyati; Kuntarti Kuntarti; Hanny Handiyanti; Titiek Muhaeriwati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to explore nurses' experiences in improving formal education at X Lampung Selatan Hospital. The method used is a phenomenological qualitative research design using a descriptive approach. The research results show that there are five themes for nurses' experience, namely: 1) Understanding of the importance of formal education for nurses; 2) Support for nurses in continuing their studies; 3) Obstacles in increasing formal education; 4) Satisfaction with the manager's efforts to support education improvement; 5) Impact of formal education improvement program. In conclusion, the nursing staff development program must be a priority in efforts to improve service quality. The role and function of the nursing manager are significant so that formal education improvement programs can run well and in line with expectations. The need for managers to provide policies and planning related to improving formal education in the form of SK, Guidelines, Guidelines, SPO, and Programs. Keywords: Formal Education, Nursing, Planning